Brexit and Uncertainty: Insights from the Decision Maker Panel1. (18th December 2018) - Bloom, Nicholas; Bunn, Philip; Chen, Scarlet; Mizen, Paul; Smietanka, Pawel; Thwaites, Greg; Young, Garry
Abstract: The UK's decision to leave the EU in the 2016 referendum created substantial uncertainty for UK businesses. The nature of this uncertainty is different from that of a typical uncertainty shock because of its length, breadth and political complexity. Consequently, a new firm‐level survey, the Decision Maker Panel (DMP), was created to investigate this, finding three key results. First, Brexit was reported to be one of the top three sources of uncertainty for around 40 per cent of UK businesses in the two years after the vote in the June 2016 referendum, and this proportion increased further in Autumn 2018. Hence, Brexit provided both a major and persistent uncertainty shock. Second, uncertainty has been higher in industries that are more dependent on trade with the EU and on EU migrant labour. Third, the uncertainties around Brexit are primarily about the impact on businesses over the longer term rather than shorter term, including uncertainty about the timing of any transition arrangements and around the nature of Brexit.